Informed consent in veterinary medicine: ethical implications for the profession and the animal 'patient' - Ashall, Vanessa; Millar, Kate M.; Hobson-West, Pru (Springer, 2018)
Informed consent processes are a vital component of both human and veterinary medicine. Current practice encourages veterinarians to learn from insights in the human medical field about how best to achieve valid consent. However, drawing on published literature in veterinary and medical ethics, this paper identifies considerable differences between the purposes of veterinary and human medical consent. Crucially, it is argued that the legal status of animal patients as ‘property’ has implications for the ethical role of veterinary informed consent and the protection of the animal ‘patient’.